2016
DOI: 10.1038/gt.2016.8
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of bionic array electric field focusing in plasmid DNA-based gene electrotransfer

Abstract: Molecular medicine through gene therapy is challenged to achieve targeted action. This is now possible utilizing bionic electrode arrays for focal delivery of naked (plasmid) DNA via gene electrotransfer. Here, we establish the properties of array-based electroporation affecting targeted gene delivery. An array with eight 300 μm platinum ring electrodes configured as a cochlear implant bionic interface was used to transduce HEK293 cell monolayers with a plasmid-DNA green fluorescent protein (GFP) reporter gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…3B, Fig. 4) confirmed the efficacy of this tandem electrode configuration (Browne et al, 2016;Pinyon et al, 2014) (Fig. 3B, C; Fig.…”
Section: Validation Of Badge ® For In Vitro and In Vivo Directed Genesupporting
confidence: 72%
See 1 more Smart Citation
“…3B, Fig. 4) confirmed the efficacy of this tandem electrode configuration (Browne et al, 2016;Pinyon et al, 2014) (Fig. 3B, C; Fig.…”
Section: Validation Of Badge ® For In Vitro and In Vivo Directed Genesupporting
confidence: 72%
“…Here it was shown that the tandem gene delivery array configuration caused a substantial compression of the electric field centre around the null between the ganged anodes and cathodes. As such, the absolute voltage in the solution in this zone was found to be very low relative to other regions around the array, but the local voltage differential (change in voltage over distance = electric field strength) was found to be equivalent to fields requiring many hundreds of volts under conventional open-field electroporation where the tissue was located between a pair of electrodes (Browne et al, 2016). This has been modelled ( Fig.…”
Section: Modelling Array-based Electric Field Focusing For Naked Dna mentioning
confidence: 98%
“…(a) 40 V pulses (5) at 50 ms duration; (b) 40 V pulses (2) at 100 ms duration; (c) 20 V pulses (5) at 50 ms duration; (d) 20 V pulses (2) at 100 ms duration configurations (below). Both these array configurations produced substantially greater gene electrotransfer than the single pairs of electrodes with the minimum (300 μm separation), with further rapid attenuation of gene transfer efficiency with increasing separation of the pairs of electrodes (Browne et al 2016). Such studies, particularly those using the higher efficiency tandem configuration, demonstrated that transduction efficiency improved as pulse duration was extended, with maximum transduction efficiency around 100 ms (Figs.…”
Section: In Vitro Close-field Electroporation Using Hek293 Cell Monolmentioning
confidence: 96%
“…The principal parameters underlying bionic array-based CFE have been characterized using a high-throughput human embryonic kidney (HEK293) cell monolayer bioassay (Browne et al 2016). Such bioassays have been effective in the past for analysis of electric fields for gene electrotransfer (Rebersek et al 2007).…”
Section: In Vitro Close-field Electroporation Using Hek293 Cell Monolmentioning
confidence: 99%
See 1 more Smart Citation